2008
DOI: 10.1111/j.1574-6941.2008.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of aquatic prokaryotic communities in the Cuatro Cienegas basin

Abstract: The Cuatro Cienegas basin (Coahuila, México) is a composite of different water systems in the middle of the desert with unusually high levels of endemism and diversity in different taxa. Although the diversity of macrobiota has been well described, little is known about the diversity and distribution of microorganisms in the oligotrophic ponds. Here we describe the extent and distribution of diversity found in aquatic prokaryotic communities by analysis of terminal restriction fragment length polymorphisms (T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
39
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 42 publications
9
39
3
Order By: Relevance
“…In addition to evidence of geographic structure within the CCB, our findings suggest high local diversity, which appears to be independent of the sampling method (Souza et al, 2006;Escalante et al, 2008). Early studies revealed a higher number of OTUs of Bacillus than would generally be expected in an oligotrophic aquatic ecosystem.…”
Section: Travelsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition to evidence of geographic structure within the CCB, our findings suggest high local diversity, which appears to be independent of the sampling method (Souza et al, 2006;Escalante et al, 2008). Early studies revealed a higher number of OTUs of Bacillus than would generally be expected in an oligotrophic aquatic ecosystem.…”
Section: Travelsupporting
confidence: 55%
“…The most plausible explanation for this apparent genetic relict of a marine life is the geographic evidence for previous ancient oceans that entered the region 200 million years ago (Alcaraz et al, , 2010Desnues et al, 2008;Moreno-Letelier et al, 2011Peimbert et al, 2012 in this issue). However, molecular clock estimation places some of the constituents of the CCB to a divergence event in the Precambrian 800 million years ago (Domínguez-Escobar et al, 2011;Moreno-Letelier et al, 2011) with subsequent colonization in the area as well as with a consistent and ongoing local speciation and diversification in the microbial community, including viruses (Desnues et al, 2008), bacteria (Escalante et al, 2008(Escalante et al, , 2009Cerritos et al, 2011;Rebollar et al, 2012), and diatoms (Winsborough et al, 2009). Thus, a significant portion of the CCB microbiota appears to have evolved from these relict ancestral marine taxa to form the extant and continuously diversifying local biota that defines a highly endemic CCB biogeographic region.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the intriguing marine ancestry of microbial communities at the CCB, we have also observed, surprisingly, that dominance by one or two species has never been found in any of our microbial diversity analyses (Souza et al, 2006;Desnues et al, 2008;Escalante et al, 2008;Cerritos et al, 2011). Instead, we have always observed even distributions, with a long tail of rare lineages, geographic differentiation ( Fig.…”
Section: The Ccb As a Model For Understanding Evolutionary Trajectorymentioning
confidence: 67%
“…Instead, we have always observed even distributions, with a long tail of rare lineages, geographic differentiation ( Fig. 1) (Escalante et al, 2008;Cerritos et al, 2011), and local endemicity. This is unusual in extreme environments where dominance is the rule (Aguilera et al, 1999;Cookson et al, 2006;Pointing et al, 2009).…”
Section: The Ccb As a Model For Understanding Evolutionary Trajectorymentioning
confidence: 99%
“…Vegetation cover and water availability in these soils depend on the degree of proximity to the aquatic systems and rainfall. Many investigations have addressed the microbial diversity of the aquatic systems of the CCB and concluded that these systems have a high microbial diversity and endemism (Souza et al, 2006;Desnues et al, 2008;Escalante et al, 2008;Breitbart et al, 2009;Cerritos et al, 2010). However, no such studies have addressed the soil microbial diversity.…”
Section: Introductionmentioning
confidence: 99%